Anti-CD2 Antibody-Coated Nanoparticles Containing IL-2 Induce NK Cells That Protect Lupus Mice via a TGF-β-Dependent Mechanism - Horwitz, David A.; Liu, Aijing; Bickerton, Sean; Castaldo, Giuseppe; Matarese, Giuseppe; Fahmy, Tarek M.; La Cava, Antonio (Frontiers in Immunology, 2020)
We recently reported that the treatment with nanoparticles (NPs) loaded with tolerogenic cytokines suppressed the manifestations of lupus-like disease induced by the transfer of donor CD4+ T cells from DBA/2 mice into (C57BL/6 × DBA/2)F1 (BDF1) mice. Although the protective effects were ascribed to the induction of adaptive CD4+ and CD8+ T regulatory cells, the results suggested that another population of immune cells could be involved. Here we report that NK cells critically contribute to the protection from lupus-like disease conferred by NPs to BDF1 mice, and that this effect is TGF-β-dependent.